Tunisia's Attitudes towards Mauritania's Independence and Its Repercussions on Tunisian-Moroccan Relations 1960-1961 - Fayyad, Neama Bahr (Journal of Tikrit University for Humanities, 2022)
Tunisian relations were characterized by fluctuation from the beginning of the formation of the two neighboring countries, and the relations between them remained a subject of controversy and suspicion between the two parties after achieving their complete independence in 1956, until the issue of the independence of Mauritania and Tunisia’s supportive position arose, which angered the Kingdom of Morocco, which was considered by its King Mohammed V, who ascended the throne of his country after its independence in 1956, that it was a hostile act aimed at eliminating Morocco’s sovereignty over its entire territory, while the Tunisian side saw that supporting the independence of Mauritania and strengthening the independence of any Arab country seeks to get rid of colonial domination regardless of its orientations and goals, hence the choice of the subject of the tagged research Tunisia’s position on the independence of Mauritania and its repercussions on Tunisian-Moroccan relations for the period 1960-1962, which included four major subjects. The third subject dealt with the Tunisian support for the independence of Mauritania, while the fourth subject dealt with the repercussions of the Tunisian attitude towards the independence of Mauritania on Tunisia’s relations with the Moroccan Kingdom.